2000
DOI: 10.1021/jp002047c
|View full text |Cite
|
Sign up to set email alerts
|

Physical Adsorption of Ar and CO2 on C60 Fullerene

Abstract: Ar and CO 2 physisorption on a very well crystallized sample of fullerene C 60 was studied by means of Monte Carlo computer simulations. Ar and CO 2 experimental isotherms were determined on high-purity C 60 to fit the potential parameters. Analysis of the structure of the adsorbed film indicated that both gases are adsorbed in the voids of the C 60 structure in a solid state with densities slightly larger than the bulk solid. Both gases exhibited a behavior similar to nitrogen. The cross-sectional area found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 12 publications
(30 reference statements)
2
15
0
Order By: Relevance
“… 3 Recently, many theoretical studies predicted that fullerene and its derivatives may provide a popular environment for gas sorption or storage, including calculation combined DFT and ab initio molecular dynamics predicting that the maximum hydrogen capacity of C60 is approximately 7.5 wt% (H58@C60), and that there are three different adsorption sites in C60 molecules for CO 2 . 4 If fullerene compounds are used as novel porous adsorbents, they may reveal superior performance in gas sorption and separation for their excellent gas binding interactions. 5 However, the sad fact is that pure fullerene is tightly packed and possesses no pores or cavities.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Recently, many theoretical studies predicted that fullerene and its derivatives may provide a popular environment for gas sorption or storage, including calculation combined DFT and ab initio molecular dynamics predicting that the maximum hydrogen capacity of C60 is approximately 7.5 wt% (H58@C60), and that there are three different adsorption sites in C60 molecules for CO 2 . 4 If fullerene compounds are used as novel porous adsorbents, they may reveal superior performance in gas sorption and separation for their excellent gas binding interactions. 5 However, the sad fact is that pure fullerene is tightly packed and possesses no pores or cavities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different mechanisms for encapsulation [2,3] and even release [1] have been proposed and studied computationally [9,10]. Deterministic computer simulations are also used to examine various phase transitions of Fullerenes [11], their melting [12], thermal disintegration [13], fragmentation from collisions [14] and physisorption onto them [15]. Extensive molecular dynamics (MD) simulations of the Fullerene formation process from the vapor phase [16 -20] show that monocyclic rings, polycyclic structures and even C 40 -C 70 closed cages can coalesce from the carbon vapor phase.…”
Section: Introductionmentioning
confidence: 99%
“…Chai and Guo [85] demonstrated that the graphitic N doped edge sites served as the active sites for CO 2 RR through DFT calculations. By Monte Carlo simulation, it was predicted that CO 2 could be absorbed in the voids of 0D C 60 fullerene [86] . When the boron was introduced into fullerene to form 1e −1 state, enhanced interaction between CO 2 and BC 59 cage was predicted through the first principle DFT calculations [87] .…”
Section: Electronic Structure Engineering By Heteroatom Dopingmentioning
confidence: 99%